ISLAM DAN LINGKUNGAN HIDUP: MENAKAR RELASI KEDUANYA - Toguan Rambe; Seva Maya Sari; Nurhayani Rambe (Prodi Studi Agama-Agama, 2021)
The environment is a global problem, in fact it is a humanitarian problem that is so complex that it is handled collectively. Population pollution is getting denser and more crowded coupled with limited natural resources and even the influence of digital media, modern technology which is often used for profit and even exploiting natural resources for personal or group gain, thus reducing the quality of nature. Islam has strong teachings about ethics towards the environment, very devastating events have often been experienced lately, namely floods, illegal logging, forest burning and the most existing ones until now are the Covid-19 epidemic, of course we realize that the impact of These incidents are very disturbing to the sustainability of the human environment.